The Discourse of Islamic Civil Society in Indonesia during The Reformation - Muhammad Saleh Tajuddin (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
The idea of civil society is still debated. Some Indonesian Muslim intellectuals state that civil society is connected with the situation at the history of Prophet Muhammad in Madinah. As Nurcholis Madjid and Dawam interpret civil society as synonymous with the Indonesian term masyarakat madani, which refers to the Islamic society in Madinah which was constructed by the prophet Mohammed. Conversely, Wahid disagrees with Madjid and Dawam's idea of Islamic civil society. Wahid’s concept of civil society is linked to his belief that the Pancasila is a more suitable ideology for the development of civil society as it is more accommodating of the ethnic and cultural diversity of Indonesia.